PENGARUH GAYA HIDUP DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN PRODUK KECANTIKAN PADA SHOPEE - Fadilah, Nur; Santoso, Budi; Rozzaid, Yusron (Jurnal Ilmu Manajemen Retail Universitas Muhammadiyah Sukabumi, 2023)
The study aims to test and analyze the effect of lifestyle and price on beauty product improvement decisions on Shopee. This type of research is quantitatively descriptive. The population in this study is students of the University of Muhammadiyah Jember Faculty of Economics Management program class of 2018 who buy beauty products through the Shoppe application. The sample was used by 90 respondents. The analysis tool uses multiple linear regressions. The results of the study proved that lifestyle and price influence the decision to buy beauty products on Shope